Infliximab therapy provides beneficial effects for choroidal thickness increase in patients with active ankylosing spondylitis: A possible mechanism mediating the suppressing of uveitis attacks - Murat KARKUCAK; Mehmet KOLA; Ahmet KALKIŞIM; Erhan ÇAPKIN; Ahmet AYAR; Adem TÜRK (Archives of Rheumatology, 2021)
Objectives: This study aims to quantitatively assess the profile of the choroidal thickness (ChT) in patients with ankylosing spondylitis (AS) using optical coherence tomography (OCT), and to examine whether the posterior eye segment abnormalities in active AS patients are reversible by infliximab therapy. Patients and methods: October 2014 and March 2016 Thirty-one patients with AS (22 males, 9 females; mean age 39.6±12.3 years; range, 22 to 68 years) and 24 healthy controls (16 males, 8 females; mean age 40.8±8.9 years; range, 35 to 61 years) were enrolled. Patients’ clinical and demographic characteristics were recorded. Using OCT, we performed retinal nerve fiber layer (RNFL) thickness, ganglion cell complex, and ChT measurements in AS patients before and six months after the initiation of infliximab therapy, and in healthy controls. Results: At baseline, patients with AS had higher ChT (mean±standard deviation: 347.5±114.4 μm) compared to healthy controls (322.1±62.8 μm), although this did not reach statistical significance level (p=0.283). At six months after the first measurement, the mean ChT was significantly decreased (under infliximab therapy: 326.5±99.7 μm vs. before: 347.5±114.4 μm, p=0.018) in AS group, while no significant change was observed in the control group (p=0.102). RNFL thickness in the AS group was significantly decreased after six months of treatment with infliximab (p=0.008). Conclusion: By evaluating the posterior eye segment of patients with AS using OCT, this study has demonstrated that active AS patients had higher ChT. The significant reduction in this ChT after infliximab therapy may be mediating the established effective suppressing action of infliximab on uveitis attacks.